Influencia de la formalización de las mypes en la determinación de los costos de producción en las empresas del sector calzado del distrito el porvenir, provincia de Trujillo, departamento de la libertad, 2014 - Ugaz Barrantes, Clara Elizabeth (2015)
After many years of considering to micro and small enterprises (Mypes) as something marginal, obsolete, or illegal, both globally and in the Peru, is beginning to recognize the real importance of the sector and its vital role in the economic and social development. From politicians to homemakers, passing through all sectors of society as well as institutions representative, accepted today than the fate of the country and the well-being of millions of people require a sector micro and small business healthy and dynamic. There are many reasons that explain this change of opinion and perspective. The present study was conducted in the district El Porvenir, province of Trujillo, Department of La Libertad, with the participation of micro and small entrepreneurs working in formal and informal way and engaged in the manufacture of footwear. The overall objective of the research is to determine the influence of the formalization of the micro and small enterprises in the determination of the production costs. In this type of companies abounds informality due to lack of information, excessive bureaucracy, fear of losing the money managed, cultural aspects, mainly. These causes to encourage, stimulate, influence and lead to the micro and small businessman to informality. To obtain information about the sample worked, applied a survey and interview questionnaire to owners of Micro and small enterprises engaged in the manufacture of footwear in the El Porvenir district. The primary objective of the micro and small enterprises is to market or expand market to make money, and to accomplish this, is essential that work in a formal way. Analyzing the results, can be confirmed the hypothesis whose statement is as follows: the formalization of Micro and small businesses positively influences the determination of the costs of production, in firms in the footwear sector in the district El Porvenir, Trujillo, La Libertad, year 2014.